1990
DOI: 10.1079/bjn19900104
|View full text |Cite
|
Sign up to set email alerts
|

Protein and energy metabolism of lactating Granadina goats

Abstract: Twelve goats of the Granadina breed in mid-and late lactation were used in two consecutive years to determine their protein and energy requirements for lactation. The animals were individually fed on diets based on pelleted lucerne (Medicago sativa) hay and barley. A total of six balance experiments were carried out. Gas exchange was measured using open-circuit respiration chambers. Milk yield ranged widely from 0.649 to 1.742 kg/d in the first year and from 0.222 to 1.989 kg/d in the second year, a steady dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 8 publications
10
47
2
1
Order By: Relevance
“…The tissue energy retained in the body was positive and did not differ between diets, even though energy content in milk was 35 kJ/kg of BW 0.75 higher in A than M. Thus, the efficiency of ME for milk production was different between diets; higher efficiency was obtained in A (0.64) than M (0.57). Different authors obtained greater values, such as Aguilera et al (1990) with lactating Granadina goats (k l = 0.67), while Bava et al (2001) found values ranging from 0.60 to 0.73 for Saanen goats during lactation. Moreover, Tovar-Luna et al (2010) investigated Alpine goats during lactation and found values ranging from 0.62 to 0.68.…”
Section: Energy Balance and Oxidation Of Nutrientsmentioning
confidence: 90%
“…The tissue energy retained in the body was positive and did not differ between diets, even though energy content in milk was 35 kJ/kg of BW 0.75 higher in A than M. Thus, the efficiency of ME for milk production was different between diets; higher efficiency was obtained in A (0.64) than M (0.57). Different authors obtained greater values, such as Aguilera et al (1990) with lactating Granadina goats (k l = 0.67), while Bava et al (2001) found values ranging from 0.60 to 0.73 for Saanen goats during lactation. Moreover, Tovar-Luna et al (2010) investigated Alpine goats during lactation and found values ranging from 0.62 to 0.68.…”
Section: Energy Balance and Oxidation Of Nutrientsmentioning
confidence: 90%
“…Water was available at all times. They were kept under identical environmental conditions except as concerns the nature and composition of the diet, which in each case was designed in accordance with the nutritional requirements and productive capacity of the species (ARC, 1980;Aguilera et al, 1990;NRC, 2007), and of their particular nutritional behaviour (Morand-Fehr et al, 1991;Boza, 2005). The health condition of the animals was supervised continuously, and any animal presenting any sign of disease was removed from the study.…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…A maior parte da informação disponível consta de extrapolações calculadas a partir de dados de bovinos (Malafaia et al 2004). Não obstante, devido a características fisiológicas especí-ficas dos ovinos e caprinos são necessários mais estudos (Aguilera et al 1990). Ainda, a dosagem de determinados elementos bioquímicos, assim como a atividade de diversas enzimas no sangue pode auxiliar no diagnóstico, no prognóstico e no acompanhamento do tratamento dos animais (Morais et al 2000).…”
Section: Introductionunclassified